Benefits of a Smart Building Design in Public Library Facilities, Lagos State, Nigeria - WOGU, Dickson Chukwuemeka; ANTHONY, Obaribiri; OTUONUYO, George; ADENUBI, Funmilola (ABUAD Journal of Engineering and Applied Sciences, 2024)
The study refers to the benefits in the adoption of a smart building design in public library facilities, Lagos State, Nigeria. Public libraries in Lagos serve as vital resources for education, information, and community activities. However, challenges such as outdated infrastructure, limited financial resources and varying levels of technological literacy among the community need to be addressed to ensure successful integration. The study examined the practicality, benefits, challenges, costs associated with integrating smart technologies and infrastructure such as smart lighting, heating, ventilation, air conditioning systems, occupancy sensors, energy management systems etc. The research methodology present in this study was sampling technique and sampling procedure, sampling frame, instrument for data collection, and data analysis techniques. The study discussed public library facilities, the criteria for categorization smart buildings, basic smart devices needed in public library buildings, problems and solutions identified with public library buildings in Lagos. The findings of this study indicated that introducing smart building design for a public library facility offers several notable benefits which include significant energy savings, improved indoor environmental quality, enhanced user experience through personalized services, and efficient space utilization. Moreover, smart building features enable real-time monitoring and data analytics for informed decision-making and maintenance. However, the challenges that needs to be addressed during the assessment process include high upfront costs, interoperability and data security concerns, potential disruptions during the transition phase, and the need of training staff to utilize the new technologies effectively. Overall, with careful planning, stakeholder involvement, and appropriate fundings, the library can embrace smart technologies to enhance its operational efficiency, user experience, sustainability, and contribute positively to the surrounding community.